Povos indígenas do Oiapoque: transformações territoriais em perspectiva sócio-histórica - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2025)
Considering the presence of indigenous populations in the municipality of Oiapoque-AP and their process of struggle for historical non-erasure, this technical report aims to present a historical analysis of the changes that marked the territorial configuration of these societies from contact with other peoples and to provide as a final product a proposal for a Didactic Sequence aimed at History teachers in basic education. Using the concept of ethnic borders, the aim is to demonstrate how relations involving indigenous peoples located in the region of the municipality of Oiapoque and non-indigenous peoples were historically constituted. To this end, the bibliography related to the subject, data from the IBGE census and the periodicals O Mensageiro and Porantim are used. It is observed that the indigenous populations: Galibi Kalinã, Galibi Marworno, Karipuna and Palikur present their own characteristics, traditions, customs and ways of life, even though located in state-referenced territory, constituted from political borders. The report points to results that demonstrate a process of historical changes that have placed indigenous peoples in a marginalized condition without recognition of their cultural and territorial rights. As a result, these peoples have joined together in organizations to resist and fight for the demarcation of their lands. In addition, it presents a proposed Didactic Sequence on the theme of the report, to meet an educational demand for public policies.
Keywords: Povos indígenas - Oiapoque (AP); Ensino de História - Direito Cultural; Ensino de História - Direito Cultural; CNPQ::CIENCIAS HUMANAS::HISTORIA::HISTORIA DO BRASIL; ODS 4 – Educação de qualidade; ODS 10 – Redução das desigualdades; ODS 16 – Paz, justiça e instituições eficazes